please explain step by step

vermonstervt

New member
Joined
Jul 24, 2005
Messages
12
simplify adding like terms
xym-3ymx+4xmy-3my+2ym Please explain step by step thanks
 
G

Guest

Guest
xym-3ymx+4xmy-3my+2ym
Notice there are like terms in this equation. So combine it.

xym-3ymx+4xmy-3my+2ym

3my and 2ym are the same. Just to let you know. So just combine like-terms and there you go. Also notice the variables xym, ymx, and xmy are the same. They're just rewritten in different order.
 

Denis

Senior Member
Joined
Feb 17, 2004
Messages
1,473
xym-3ymx+4xmy-3my+2ym

rewrite (2*5*3 = 2*3*5, right?):
mxy - 3mxy + 4mxy - 3my + 2my : ok?

now polish off: 2mxy - my
 

vermonstervt

New member
Joined
Jul 24, 2005
Messages
12
Is this correct

-a(b-a) if a=-4 b=-3
-4(1)=-4
If not correct please explain step by step thanks:)
 

stapel

Super Moderator
Staff member
Joined
Feb 4, 2004
Messages
15,943
Please post new questions as new threads, not as replies to old questions. Thank you.

Eliz.
 

vermonstervt

New member
Joined
Jul 24, 2005
Messages
12
Are these correct

a^2-b^2a if a=-2 b=3
-2^2-3^2-2
-4-4-2=-13-2=-15
------------------
-x^2-y^3 if x=-3 y=-2
-3^2-2^3
-9-8=-17
 

Gene

Senior Member
Joined
Oct 8, 2003
Messages
1,904
Please post new questions as new threads, not as replies to old questions. Thank you.


You have the right idea but are careless with your signs. -a(b-a) if a=-4 b=-3
-(-4)((-3)-(-4)) =
(4)(1) = 4

Study this one then try the next one again keeping the variables in ()s whenyou substitue.
 
G

Guest

Guest
it doen't matter the order in which three variables are put to get an answer.

say that x=5,
y=3
& m= 2.

the order in which the 3 numbers would be multiplyed wouldn't affect the result.

5 times 3 times 2 will equal 30
and so will
3 times 2 times 5.


Now,
knowing that,
xym is the same thign as ymx and the same thing as xmy,

if xym=ymx

then xym(also ymx) + 3ymx would = 4 ymx. Right? follow with me here.


Then, concluding everything else i explained, then 4 ymx would be the same thing as 4xmy.

so,

4ymx(also 4xmy) + 4xmy= 8 xmy.


_____________________________________________


Part 2.

now the other part of the equation left would be 3my+2ym.

Since that whole part is SUBTRACTED from the other half,
you need to simplify that part seperately from the other part.

as i said, before, 3my could be the same thing as 3ym, so
3my(also 3ym) + 2ym= 5ym.





:?: :idea: :!: THE ANSWER IS::: 8xmy-5ym
 
G

Guest

Guest
NOW EVERYONE!!!
stop messing with the problem ANYMORE> thankyou.
 

stapel

Super Moderator
Staff member
Joined
Feb 4, 2004
Messages
15,943
beautifull_love101 said:
NOW EVERYONE!!!
stop messing with the problem ANYMORE> thankyou.
Um... you're the only one "messing" with threads. Kindly start helping people, or else please take your chat-room behavior elsewhere. Thank you.

Eliz.
 
Top